(untitled) (Journal of Medicine, 2016)
Nasal foreign bodies are rare events occurring mostly in children. However they can be seen in adults as a result of trauma resulting from road traffic accidents and bullet injuries. However these foreign bodies, if associated with high velocity, can cause greater harm at skull base by casing injury to vital structures. Hence safe planning and removal is warranted. We present a case of a 48 year old female with an impacted metallic foreign body in the sphenoid. Endoscopic removal of the foreign body was was done. J MEDICINE July 2016; 17 (2) : 115-117